Critical review of drug promotional literature using the World Health Organization guidelines - Puttaswamy Ganashree; Krishnaswamy Bhuvana; Narayana Sarala (Wolters Kluwer Medknow Publications, 2016)
Objective: Drug promotional literatures (DPLs) are used as a promotional tool to advertise new drugs entering the market to doctors. The objective of the present study is to evaluate the accuracy of DPLs by using the World Health Organization (WHO) criteria. Methods: An observational study was conducted from March to August 2014. The DPLs were collected from various departments at R.L. Jalappa Hospital and Research Centre attached to Sri Devaraj Urs Medical College, Kolar, India. The literature was evaluated based on 11 criteria laid down by the WHO. Findings: Two-hundred DPLs were evaluated. Cardiovascular drugs (34 [17%]) were promoted the most, followed by antidiabetic drugs (31 [15.5%]) and antimicrobial agents (29 [14.5%]). Single drug was promoted in 134 (67%) and fixed drug combination in 66 (33%) brochures. Manufacturer's name was mentioned in 194 (97%), but their address was mentioned in 109 (54.5%) claims only. Drug cost was revealed only in 12 (6%) DPLs. Each ingredient's generic name, brand name, and dosage form were mentioned in 197 (98%) brochures. Indication for use was stated in 193 (96.5%) claims. Contraindications, adverse effects, precautions, and drug interactions were listed in 68 (34.5%), 65 (32.5%), 65 (32.5%), and 58 (29%) advertisements. References were cited in 133 (66.5%) brochures. Only 63 (31.5%) literatures had relevant pictures of drugs being promoted and 59 (29.5%) had a graphical representation of pharmacological properties. A total of 131 (69%) DPLs followed 50% of the WHO criteria. Conclusion: Majority of DPLs satisfied only half of the WHO criteria for rational drug promotion and none of them fulfilled all the specified criteria. Incomplete or exaggerated information in DPLs may mislead and result in irrational prescription. Therefore, physicians should critically evaluate DPLs regarding updated scientific evidence required for quality patient care.